MENTAL NURSING CARE FOR MR. E WITH A FOCUS ON THE INTERVENTION OF PROVIDING MUROTAL PSYCHORELIGIOUS THERAPY OF THE QUR'AN TO CONTROL AUDITORY HALLUCINATIONS AT RSJD DR. ARIF ZAINUDDIN SURAKARTA - rahma wati (The Shine Cahaya Dunia D-III Keperawatan, 2023)
Background:  The number of people with mental disorders in Indonesia has increased 7 per million households, this figure shows that every 1000 households there are 7 people with mental disorders, so this number is estimated to reach 450,000 people suffering from mental disorders (Ministry of Health, 2018). In 2019, Central Java had 81,983 people with mental disorders (Central Java Provincial Health Office, 2019). Based on the results of the medical recap of RSJD dr. Arif Zainudin Surakarta from March 2022 to January 2023, data on mental disorder clients were obtained as many as 40475, namely 32951 clients with hallucinations. The effect if not immediately addressed is a loss of self-control. Treatment of hallucinatory patients with pharmacological and nonpharmacological methods, namely Murottal Qur'an. The purpose of the study was to provide mental nursing care to Mr. E with a focus on the intervention of providing Qur'anic murotal psychoreligious therapy to control auditory hallucinations at RSJD Dr. Arif Zainuddin Surakarta.Methodology: The type of research used in this paper is quantitative with a descriptive approach. The design used in the research is a case study. The research subject is Mr. E schizophrenic patient with delusional hallucinatory disorders.Results: Researchers identified, after doing Qur'anic Murotal Psychoreligious Therapy for 7 days in the morning and evening, patient was able to overcome his hallucinations, feelings became calmer and less anxious.Conclusion: There is an effect on the effectiveness of Qur'anic Murotal Psychoreligious Therapy to reduce hallucinations in patients.Keywords: hallucinations, psychoreligious therapy, murotal QuranBibliography: 8 (2010-2023)